SISTEM INFORMASI PENJUALAN BERBASIS ANDROID BAGI UKM RETAILER DI KELURAHAN KANDANG LIMUN KOTA BENGKULU - Apri Andani; Basuki Sigit Priyono; Rusdi Efendi (DHARMA RAFLESIA, 2018)
The purposes of this community service are to improve SME’s owner’s skill in using simple technology for their business and to amend their inventories and sales management by using Android Management Information System Application. This community service was conducted in Kandang Limun, Bengkulu City, in 2017. The target society was the owners of SME retails around location. There were 15 owners of SME retails. The methods used were persuasive approach, demonstrations and practices, accompaniment, and evaluation. The content of training were simple financial report recording and i-REAP and Barcode application by Android. The result shows that this activity was done well. Each step was followed seriously by the participants. After training, 50% of the owners still applied simple accounting recording, 30% owners used i-REAP, and 20% owners used both. Finally after accepting this training, 100% owners who used both manual accounting recording and i-REAP were able to know the amount of goods inventory and sales better than before accepting the training. Keywords: android, sales information system, i-REAP